A priority based job scheduling algorithm in cloud computing - Shamsollah, Ghanbari; Othman, Mohamed (2012)
Nowadays cloud computing has become a popular platform for scientific applications. Cloud computing intends to share a large scale resources and equipments of computation, storage, information and knowledge for scientific researches. Job scheduling algorithms is one of the most challenging theoretical issues in the cloud computing area. Some intensive researches have been done in the area of job scheduling of cloud computing. In this paper we have proposed a new priority based job scheduling algorithm (PJSC) in cloud computing. The proposed algorithm is based on multiple criteria decision making model.